Transparência pública: ampliação dos conjuntos de dados do Portal de Dados Abertos da Universidade Federal do Rio Grande do Norte - Oliveira, Alanna Siqueira Simonetti (2023)
Increasingly, citizens have actively participated in public management. This protagonist role has been greatly strengthened due to the opening of government data that encourages social control and fosters democratic accountability by enabling an evaluation of the public administration's actions and their respective consonance with the achievement of social objectives; crucial for the effective exercise of citizenship. Under this perspective that combines the information dissemination to the consolidation of democracy, this dissertation aims to analyze the demands of the Platform Fala.BR - Access to Information Law for the years 2019, 2020 and 2021 in order to suggest the creation of new open format datasets in the Open Data Portal of the Federal University of Rio Grande do Norte in Brazil. The research is grounded in theoretical, conceptual aspects and in critical and correlational approaches regarding public transparency and open data. As for the research's methodological procedures, it is of a descriptive exploratory study that used indirect documentation as a technical procedure, which was carried out through the documentary research technique. Bibliographic research was also used to substantiate the study, and the content analysis proposed by Bardin (2011), whichguided the identification of the the most required topics by citizens that could be made available in open format. As for the analysis carried out, the research brought as a result, the possibility of significant expansion of the data available on the Open Data Portal of the forementioned university, which included the creation of two new groups, nineteen new sets, as well as the improvement of six sets of existing open data from the insertion of new information. It is envisioned that this research will lead to an increase in the promotion of transparency within the Federal University of Rio Grande do Norte by enhancing citizens' access to information and, consequently, social participation, as well as by providing a referential basis that may inform the creation of the next Open Data Plan. Under this perspective, it is expected that this study, serves as a beacon for the improvement of the disclosure of open government data, contributes to corroborate the importance of this type of data as an instrument of realization of fundamental rights which precepts human dignity, freedom and equality and which are the mainstay of the democratic rule of law.